Validation of the Eyesi Slit Lamp Simulator for a Simulated Training Curriculum for Residents in Ophthalmology: A National Delphi study - Kasper Ruotsalainen Hansen; Simon Joel Lowater; Kristina Sanne Lyngsø; Anne Helene Køllund Nissen; Anna Stage Vergmann (Ophthalmology and Therapy)
Abstract Introduction Simulation-based training is increasingly used in medical education to improve clinical skills. The Eyesi slit lamp simulator offers a platform for training in slit lamp examination and indirect ophthalmoscopy. However, training needs to be evidence-based to ensure reliable evaluation. Therefore, this study aims to identify relevant training modules on the Eyesi slit lamp simulator for ophthalmology residents through a national Delphi study to develop a training curriculum. Methods A two-round Delphi study was conducted with chief physicians, consultants, and professors involved in ophthalmology residency training across Denmark. In round one, experts evaluated the relevance of training modules on the Eyesi slit lamp simulator using a binary scale, and modules achieving ≥ 75% in relevance were included in round two. In round two, these modules were rated on a linear scale (1–5) for detailed assessment. Consensus was defined by a standard deviation (SD) < 1.0 and interquartile ranges (IQR) were calculated to assess variability and identify outliers. Results A total of 11 experts participated in round one (response rate: 84.6%), and 8 experts participated in round two (response rate: 72.7%). In round one, a strong expert agreement on module relevance was found. In round two, all modules achieved a mean ranking > 3.0, with the lowest being 3.9. Modules with a mean ranking > 3.0 were considered relevant and included in the final analysis. Two modules had an SD > 1.0, indicating a lack of consensus. Conclusions This study established expert consensus on 32 essential training modules for the Eyesi slit lamp simulator, supporting their integration into an ophthalmology residency curriculum. Further testing under an evidence-based framework is required to integrate them into a structured curriculum and assess their impact on clinical skills.